PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL PADA NILAI PERUSAHAAN - Damayanti, Ni Putu Wida Putri; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
Prosperity shareholders optimally achieved through an increase in the value of the company. Good corporate governance mechanisms based on managerial ownership and institutional ownership are directed to achieve this. The purpose of this study was to examine the effect of managerial ownership and institutional ownership on the value of companies listed on the Indonesia Stock Exchange. Based on purposive sampling method, 16 samples were used as samples. Techniques of analysis in this study is multiple regression analysis. The statistical result states that managerial ownership has no effect on firm value, while institutional ownership has a positive effect on firm value.
Keywords: enterprise value, managerial ownership, institutional ownership